Developing an Instructional Package of Environmental Education (EnMor Book) Based On Ecology In Improving Student’s Environmental Moral Behavior - Imelda Hutasoit (Universitas Negeri Jakarta, 2017)
This research is aimed at developing an ecological based of instructional package in improving student Environmental Moral Behavior (EMB). So, in this case, Research and Development has been applied by involving n = 25 students at Govermental Institute of Home Affairs as a treatment group and 25 more students as a control group. EMB has been measured by administering an instrument with 31 items which empirically valid and its reliability is .905. Hypothesis has been tested by applying correlated and independent t-test. Research result reveals that the instructional package has been proven effectively and significantly improve student EMB. Therefore, if student’s EMB could be improved, then this instructional package is beneficial to be implemented. This is one of the efforts in trying to enhance positive EMB by introducing them basic knowledge about ecology.